Comparison of Two Different Scheimpflug Devices in the Detection of Keratoconus, Regular Astigmatism, and Healthy Corneas - David Finis; Bernhard Ralla; Maria Karbe; Maria Borrelli; Stefan Schrader; Gerd Geerling (Journal of Ophthalmology)
Aim. The aim of this study was to determine the intra- and interobserver variability of two Scheimpflug based camera systems, Pentacam and Sirius. In addition, the comparability of the measurements was tested in healthy subjects, subjects with regular astigmatism, and keratoconus patients. Methods. Intra- and interobserver variability were assessed in 20 healthy corneas. Pachymetry values were also compared with ultrasound pachymetry as a reference measurement. To detect possible differences between the two devices, 82 eyes with clinically established keratoconus, 30 eyes with regular astigmatism (>1.5 D), and 60 eyes without corneal pathologies were included in this prospective study. Results. Pachymetry and keratometry showed good intra- and interobserver variability for both devices. Pachymetry values obtained with the Sirius system (579±58 μm) were significantly higher compared to the Pentacam system (551±40 μm, P<0.001) and to ultrasound pachymetry (550±43 μm, P<0.001). Significant interdevice differences were found regarding the majority of the detected keratometry parameters. Conclusions. Both devices show almost perfect reproducibility in healthy subjects. However, pachymetry and keratometry values of the two devices should not be used interchangeably.